A Comparison of Contemporary Human Resource Management and Employment Relations Practices of Japanese and US Multinational Corporation Subsidiaries: Evidence from Four Countries - Bartram, Timothy; Adam, Duncan; Edwards, Tony; Jalette, Patrice; Burgess, John; Stanton, Pauline (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2019)
This paper compares Japanese and US multinational corporations (MNCs) on their deployment of human resource management (HRM) and employment relations (ER) practices within four countries. Debate about convergence is used to reconcile findings. The context is the shift from the dominance of the Japanese economy in the 1980s and early 1990s towards the renewed dominance of the US economy in more recent decades. We draw on data from representative, parallel surveys of MNCs operating in Canada, the UK, Spain and Australia to test a set of hypotheses examining similarities and differences between subsidiaries of Japanese and US MNCs in relation to management control across borders, remuneration, representation and worker involvement.The findings demonstrate that, despite the pressures of globalization, and the partial movement away from traditional Japanese management practices in Japan, there are clear country of origin effects for Japanese and American MNCs. Results indicate that Japanese and US MNCs behave differently in terms of the control that they exercise, with Japanese firms exhibiting a greater tendency to use personal forms of control in their foreign subsidiaries and a lower tendency to use procedural forms of control. In terms of HRM practices, Japanese MNCs are distinctive in relation to pay systems. For example, they are less likely than their US counterparts to use performance-related pay and, more likely, to adopt non-union representative structures in subsidiaries.In line with Kaufman (2016), we argue that the study’s findings provide evidence for the ‘converging divergence phenomenon’ in that both Japanese and US MNCs are adopting the most universal aspects of each other’s management practices and integrating them into their own unique systems of management in response to global market forces. We discuss the theoretical implications for the convergence and divergence of HRM and ER systems, and the development of such systems in Japanese and US MNC subsidiaries.